2014
DOI: 10.1186/1472-6963-14-317
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and emotional distress in patients with dizziness: a cross-sectional approach to disentangle their relationship

Abstract: BackgroundDizziness is frequently encountered in medical practice, often takes a chronic course and can impair the health related quality of life (HRQoL). However results on the extent of this impairment of HRQoL are mixed. Furthermore, the relationship between dizziness and the HRQoL is only partially understood. The role of clinical symptoms of dizziness and psychosocial factors such as emotional distress on this relationship is for the most part unknown.MethodsThe cross-sectional study evaluated the HRQoL i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
67
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 47 publications
5
67
0
7
Order By: Relevance
“…Although the DHI scores for the clinical group were significantly higher than controls, the mean score for the clinical group suggests that the impact of dizziness on quality of life was relatively mild for most participants. Each subcategory score (physical, functional, and emotional) was higher than controls, and some people with VS were moderately (36–62) impacted by symptoms, consistent with other vestibular disorders . These findings are not surprising, as people with vestibular disorders may have abnormal sensitivity to motion .…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Although the DHI scores for the clinical group were significantly higher than controls, the mean score for the clinical group suggests that the impact of dizziness on quality of life was relatively mild for most participants. Each subcategory score (physical, functional, and emotional) was higher than controls, and some people with VS were moderately (36–62) impacted by symptoms, consistent with other vestibular disorders . These findings are not surprising, as people with vestibular disorders may have abnormal sensitivity to motion .…”
Section: Discussionmentioning
confidence: 54%
“…Each subcategory score (physical, functional, and emotional) was higher than controls, and some people with VS were moderately (36-62) impacted by symptoms, consistent with other vestibular disorders. 18,[31][32][33] These findings are not surprising, as people with vestibular disorders may have abnormal sensitivity to motion. 18 If persistent symptoms contribute to distress or depression, counseling is indicated in addition to management of physical and functional deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Dizziness symptoms were reported in 1 out of 5 individuals of working age (Yardley et al, 1998). It is reported that health-related quality of life, both mental and physical, is significantly impaired in those with dizziness (Weidt et al, 2014). Although dizziness can be caused by a variety of medical conditions, it is estimated that 50% of cases are due to vestibular dysfunction (Hall and Cox, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the greater prevalence of vestibular loss in older adults and its associated functional limitations, the quality of life (QoL) burden of vestibular loss in this vulnerable population has not been well-studied. The few studies that have reported QoL outcomes considered the broader symptom of dizziness rather than specifically vestibular physiologic impairment, 7,[11][12][13][14][15] did not have a normative-age-matched comparison group available, 11 or were conducted across a broad age range including younger age groups. 7,13,16 In this report, we quantify the independent impact of vestibular physiologic loss on overall QoL and identify domains of health including vision, hearing, speech, ambulation, dexterity, emotion, cognition, and pain affected by this condition in a sample of older adults with vestibular loss seen in a Neurotology clinic.…”
Section: Introductionmentioning
confidence: 99%